An investigation of Prospective Teachers’ Reasons for Preferring Teaching as a Progression: Turkish Context: Teaching Profession, Pedagogical Formation Education Certificate Program - Kaya, Halil İbrahim; Korucuk, Murat (GIST – Education and Learning Research Journal, 2022)
This study aimed to reveal the reasons for choosing the teaching profession of pedagogical formation education certificate program students and to examine the differences in the reasons for choosing teaching according to gender, place of residence, high school, monthly income of the family, parental education level and order of preference variables. The survey model was used. The universe consisted of approximately 250 pedagogical formation education certificate program students studying at a University in Eastern Anatolia in Turkey in 2022. The sample consists of 158 randomly selected pedagogical formation education certificate program students. The “Reasons for Choosing Teaching as a Career Scale”, which was developped by Lai, Chan, Ko, and So in 2005 and adapted into Turkish by Balyer and Özcan in 2014, was used as a data collection tool. As a result of the study, it was seen that the level of choosing to teach for internal reasons of pedagogical formation education certificate program students was higher than the level of choice for external reasons and the level of being affected by (others). In addition, it was concluded that the reasons for choosing the teaching profession of pedagogical formation education certificate program students differed according to gender, place of residence, income, order of preference, and education level of parents.